2011
DOI: 10.1016/j.plefa.2010.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids modulate collagen signaling in human platelets

Abstract: SummaryDietary intake of the omega-3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) results in cardioprotective benefits. However, the cellular and physiological basis for these benefits remains unclear. We hypothesized that EPA and DHA treatment would interfere with collagen-mediated platelet signaling. Thirty healthy volunteers received 28 days of 3.4 g/d EPA +DHA with and without a single dose of aspirin. Clinical hematologic parameters were then measured along with assays of collage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
34
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 38 publications
(38 reference statements)
4
34
1
Order By: Relevance
“…The study of Larson et al [21] showed that omega-3 fatty acids in a daily dose of 3.4 g may modulate collagen signaling in human platelets. Our observations did not reveal any difference in COL test results after the administration of 1.0 g N-3 PUFA.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Larson et al [21] showed that omega-3 fatty acids in a daily dose of 3.4 g may modulate collagen signaling in human platelets. Our observations did not reveal any difference in COL test results after the administration of 1.0 g N-3 PUFA.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain very mild changes (if any) of several platelet biomarkers observed in our study. Finally, a recent elegant study [31] suggested that 28 days of PO-3A therapy was associated with a moderate reduction of collagen-mediated platelet signaling. Importantly, PO-3A had no impact on PFA-100 readings when an ADP/Collagen cartridge was used, but decreased platelet expression of GP IIb/IIIa, and P-selectin significantly [31].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a recent elegant study [31] suggested that 28 days of PO-3A therapy was associated with a moderate reduction of collagen-mediated platelet signaling. Importantly, PO-3A had no impact on PFA-100 readings when an ADP/Collagen cartridge was used, but decreased platelet expression of GP IIb/IIIa, and P-selectin significantly [31]. These changes were identical to our data, and suggest that platelet inhibition is a ‘real deal’ rather than a laboratory artefact.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that antiplatelet properties of omega-3 PUFA as monotherapy are negligible, but become apparent when they are used in combination with other antiplatelet agents [6][7][8] . It has been shown that omega-3 PUFA facilitate aspirin-induced platelet inhibition both in healthy volunteers [7] and CAD patients [6] .…”
mentioning
confidence: 99%
“…It has been shown that omega-3 PUFA facilitate aspirin-induced platelet inhibition both in healthy volunteers [7] and CAD patients [6] . It has also been demonstrated that the addition of omega-3 ethyl esters to the combination of aspirin and clopidogrel significantly potentiates platelet response to clopidogrel after percutaneous coronary intervention in optimally medically treated patients [8] .…”
mentioning
confidence: 99%